La temática de los universales y su presencia en la cristología de algunos autores - Pardo Fariña, Felipe (Veritas, 2013)
The author begins by defining the concepts of singular and universal, continuing with a historical review regarding their use in the thought of some philosophers, in order to finally establish the connection between the universal and the singular referred to Jesus Christ in the plot of some Christologies.